2001
DOI: 10.1038/ncb731
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β induces apoptosis through Smad-mediated expression of DAP-kinase

Abstract: Transforming growth factor-beta (TGF-beta) and TGF-beta-related factors induce apoptosis in a variety of tissues; however, the mechanism underlying this induction is largely unknown. Here, we demonstrate that TGF-beta induces the expression of the death-associated protein kinase (DAP-kinase) as an immediate early response in cells that undergo apoptosis in response to TGF-beta. DAP-kinase is a positive mediator of apoptosis induced by certain cytokines and oncogenes. We show that the DAP-kinase promoter is act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
285
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(297 citation statements)
references
References 47 publications
9
285
1
2
Order By: Relevance
“…In other HCC cell lines, TGF-b1 induced apoptosis of Hep3B but not of HepG2 cells (Jang et al, 2002;Zhang et al, 2004). We have observed that PDCD4 expression was upregulated in Hep3B but rarely in HepG2 cells by TGF-b1 treatment (unpublished data).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In other HCC cell lines, TGF-b1 induced apoptosis of Hep3B but not of HepG2 cells (Jang et al, 2002;Zhang et al, 2004). We have observed that PDCD4 expression was upregulated in Hep3B but rarely in HepG2 cells by TGF-b1 treatment (unpublished data).…”
Section: Discussionmentioning
confidence: 68%
“…In our present data, PDCD4-antisense expression was less effective for the recovery of cell growth inhibited by TGF-b1 than for that by Smad7 (compare Figures 6b and 8b) despite PDCD4 expression was almost depressed by the antisense construct. A different signaling pathway also might be present in the TGF-b1-induced apoptosis of Huh7 cells as shown in Hep3B (Jang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, death associating protein (DAP) kinase, which induces apoptosis in certain cell types, was found to be transcriptionally induced by the TGF-b/Smad pathway. Inhibition of DAP kinase activity protected the cells from TGF-b-induced apoptosis (Jang et al, 2002).…”
Section: Regulation Of Apoptosis By Smadsmentioning
confidence: 99%
“…4 In contrast, TGF-b-induced type-I cell death is mediated by DAPk in a p53-independent manner. 5 Another mode of programmed cell death in which DAPk is involved in some cellular settings is autophagic type-II cell death, characterized by the formation of double-membrane vesicles that consume cell contents. 6 Overexpression of DAPk leads, in some cells, to the appearance of autophagic vesicles and cell death that does not involve activation of caspases.…”
mentioning
confidence: 99%